O Colégio Estadual Manoel Ribas e o ensino secundário público em Santa Maria - Romero, Maria Helena Nascimento (2025)
This thesis is within the field of the History of Education, developed in the Postgraduate Program in History (PPGH) of the Federal University of Santa Maria/UFSM, area of concentration: “History, Power and Culture” and the Line of Research: “Memory and Heritage”. With the title “Manoel Ribas State School and Public Secondary Education in Santa Maria”. Its central theme was public secondary education in Santa Maria, in the state of Rio Grande do Sul (RS). The general objective is to understand and reconstruct the history of Manoel Ribas State School. The choice for this institution is justified because it was the first public and state school created in Santa Maria/RS. The time frame covers the period from 1953 to 1963, marked by the foundation of Colégio Estadual Manoel Ribas, with Father Rômulo Zanchi as its first principal, and his departure from the management. The research is based on the theoretical field of History of Education, with a specialty in History of School Institutions. For its construction, documentary research (in textual and iconographic documents and journalistic sources) and bibliographic research were carried out. From the used sources, it was possible to observe that Colégio Estadual Manoel Ribas played a leading and active role in the creation and development of free, coeducational, three-shift public Secondary Education in the municipality of Santa Maria. Therefore, it is concluded that this educational institution, belonging to the State of Rio Grande do Sul, since its installation in Santa Maria, has sought to innovate in education, accepting risks and knowing how to value the availability of human and material resources in order to, in this way, modify the economic and social context of the municipality. This process began with the implementation of the Junior High School and the Scientific School in 1954, followed by the creation of the city's first free night-time Junior High School in 1956. Later, in 1960, the school played a decisive role in establishing the Classical Course, which was the only free and mixed course in Santa Maria at the time. In addition, it also indirectly contributed to the development and consolidation of Higher Education in the city, as many students participated in the first classes of the University of Santa Maria/Federal University of Santa Maria in significant numbers. Thus, it was concluded that the secondary education context of Santa Maria was strongly influenced and modified after the creation of the Manoel Ribas State School.